Papato e monachesimo "esente" nei secoli centrali del Medioevo - D'Acunto, Nicolangelo (Reti Medievali E-Book, 2003)
In the XI-XIII centuries the monasteries experienced a bigger freedom from the interference of the dioceses and were able to benefit from the exemption to interact with the local dominant classes. This new dynamic in relationships had an impact on the transformations of both the ecclesiastical structures and the political and economic assets in the territory. The authors analyse the phenomenon from different points of view, always paying attention to the sources and addressing topics such as: the interventions of the papacy in order to influence the constitutional configuration of Orders and congregations; the forms of the documents issued for this purpose by the pontifical chancery; the intricate relations between the papacy, bishops and exempt monasteries; the relationships between the latter and local societies.